Control of Cell Alignment and Morphology by Redesigning ECM‐Mimetic Nanotopography on Multilayer Membranes. Issue 15 (29th March 2017) - Sousa, Maria P.; Caridade, Sofia G.; Mano, João F.
Abstract : Inspired by native extracellular matrix (ECM) together with the multilevel architecture observed in nature, a material which topography recapitulates topographic features of the ECM and the internal architecture mimics the biological materials organization is engineered. The nanopatterned design along the XY plane is combined with a nanostructured organization along the Z axis on freestanding membranes prepared by layer‐by‐layer deposition of chitosan and chondroitin sulfate. Cellular behavior is monitored using two different mammalian cell lines, fibroblasts (L929) and myoblasts (C2C12), in order to perceive the response to topography. Viability, proliferation, and morphology of L929 are sensitively controlled by topography; also differentiation of C2C12 into myotubes is influenced by the presence of nanogrooves. This kind of nanopatterned structure has also been associated with strong cellular alignment. To the best of the knowledge, it is the first time that such a straightforward and inexpensive strategy is proposed to produce nanopatterned freestanding multilayer membranes. Controlling cellular alignment plays a critical role in many human tissues, such as muscles, nerves, or blood vessels, so these membranes can be potentially useful in specific tissue regeneration strategies. Abstract : Flexible and freestanding biomimetic multilayer membranes, which topography resemble the nanofeatures of the extracellular matrix, are successfully developed using a friendly user layer‐by‐layer technology. The ability to crosslink with genipin as well as the presence of a patterned topography on the surface of the natural‐based membranes provides a promising system to tailor cellular behavior including cell alignment and differentiation.